Three-Dimensional Live Imaging of Bovine Preimplantation Embryos: A New Method for IVF Embryo Evaluation - Masuda, Yasumitsu; Hasebe, Ryo; Kuromi, Yasushi; Kobayashi, Masayoshi; Urataki, Kanako; Hishinuma, Mitsugu; Ohbayashi, Tetsuya; Nishimura, Ryo (Frontiers in Veterinary Science, 2021)
Conception rates for transferred bovine embryos are lower than those for artificial insemination. Since embryo transfer (ET) is widely used in cattle but many of the transferred embryos fail to develop, a more effective method for selecting bovine embryos suitable for ET is required. To evaluate the developmental potential of bovine preimplantation embryos (2-cell stage and blastocysts), we have used a non-invasive method of optical coherence tomography (OCT) for obtaining live images. The images were used to evaluate 22 parameters of blastocysts, such as volumes of inner cell mass and thicknesses of trophectoderm (TE). Bovine embryos were obtained by in vitro fertilization (IVF) of the cumulus-oocyte complexes aspirated by ovum pick-up from Japanese Black cattle. The quality of the blastocysts was examined under an inverted microscope and all were confirmed to be Code1 according to the International Embryo Transfer Society standards for embryo evaluation. The OCT images of embryos were taken at the 2-cell stage and at the blastocyst stage prior to transfer. In OCT, the embryos were irradiated with near-infrared for a few minutes to capture three-dimensional images. Nuclei of the 2-cell stage embryos were clearly observed by OCT, and poly-nuclear cells at the 2-cell stage were also clearly found. With OCT, we were able to observe embryos at the blastocyst stage and evaluate their parameters. The conception rate following OCT (15/30; 50%) is typical for ETs and no newborn calves showed neonatal overgrowth and death, indicating that OCT did not adversely affect ET. A principal components analysis was unable to identify parameters associated with pregnancy, while by using hierarchical clustering analysis, TE volume has been suggested to be one of the parameters for the evaluation of bovine embryo. At present, OCT imaging should be used for investigating the time-dependent changes of IVF embryos, and with further improvements could become a useful tool for selection of high-quality embryos for transfer.